Primární maligní nádory kostí u dětí možnosti záchovné chirurgie s využitím aloštěpů - Vlach, Martin; Schovanec, Jiří; Havlas, Vojtěch; Wagenknecht, Lukáš; Trč, Tomáš (Casopis lekaru ceskych, 2016)
Therapy of primary malignant bone tumors is always multimodal and requires close cooperation of oncologist, orthopedic surgeon, radiologist and others. In our article, we provide a brief overview of the most common malignant bone tumors in pediatric patients and summarize the commonly used therapeutic procedures. Despite advances in cancer treatment radical surgical resection of the tumor is still necessary. If possible, it should be complete removal of the affected structures, made in terms of the so-called limb-saving (limb-sparing) surgery that preserves the shape and function of the affected limb to the fullest extent possible. In addition the resection must be done at the same time with substitution of the removed bone. Bone grafts, both autografts and allografts, are used in majority of solutions. We also discuss the comparison of different approaches of limb-saving surgery compared to ablative procedures.
Keywords: Limb Salvage; osteosarcoma Ewing sarcoma.; nádory kostí; Sarcoma, Ewing; Humans; paediatrics; Ewingův sarkom; ortopedické výkony; transplantace kostí; bone; lidé; záchrana končetiny; Bone Transplantation; osteosarkom; malignant tumor; Allografts; alografty; Orthopedic Procedures; Osteosarcoma; Bone Neoplasms